Solvability of Impulsive Nonlinear Partial Differential Equations with Nonlocal Conditions - Jabbar, Ali Kadhim; Hasan, Sameer Qasim (Iraqi Journal of Science, 2020)
The aim of this paper is to investigate the theoretical approach for solvability of impulsive abstract Cauchy problem for impulsive nonlinear fractional order partial differential equations with nonlocal conditions, where the nonlinear extensible beam equation is a particular application case of this problem.